Reimagining Value-Based Special School Leadership in the Digital Era: An Exploratory Study - Rendy Wikrama Wardana; Fitri April Yanti; Afrizal Mayub; Noorzana Khamis; M. Anas Thohir; Elza Heryensi; Rinda Fitri Handayani (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
In the digital age, schools must rethink their leadership approaches to address student diversity, particularly for learners with Special Educational Needs (SEN), to build inclusive learning environments. This qualitative exploratory study examines how junior high school leaders in special schools interpret and implement inclusive digital leadership to support SEN students’ learning experiences. Data were collected through semi-structured interviews with school leaders, including principals, vice principals (curriculum/academic affairs), ICT coordinators, special education teachers, and subject teachers involved in inclusive classrooms. Additional data were obtained through non-participant observations at three special junior high schools and through analysis of policy documents on digital inclusion. Trustworthiness was ensured through source triangulation, member checking, and Braun and Clarke’s thematic analysis. Findings reveal that inclusive digital leadership is characterized by three main practices: values-based leadership emphasizing fairness and equity; strategic development of digital capacity for all stakeholders through continuous professional learning and collaboration; and adaptive governance supported by technology, data-informed decision-making, and personalized accommodations for SEN learners. Despite progress, leaders face challenges such as limited teacher digital competence, inadequate infrastructure, and inconsistent policy implementation. This study highlights the importance of strengthening inclusive digital leadership capacity to ensure equitable and meaningful learning for SEN students. Practical implications include designing targeted leadership development programs, fostering collaboration among stakeholders, and establishing flexible, sustainable governance models. Future research should focus on developing and testing structured frameworks for values-based digital leadership in special schools, emphasizing measurable improvements in ethical decision-making, inclusive data practices, and technology-supported professional learning systems.